(untitled) (Boletin Médico de Postgrado, 2022)
Moringa oleifera is a tree native to certain regions of Asia and Africa, rich in proteins, vitamin A, minerals, essential amino acids, antioxidants and flavonoids. M. oleifera extracts exhibit anti-inflammatory, antioxidant, hepatoprotective, neuroprotective, hypoglycemic and antimicrobial effects. Two clinical cases of diabetic patients with infectious processes in the foot and hand are presented, who had received antibiotic treatment without satisfactory response, for which they were treated with a poultice of M. oleifera three times a day, with a duration of 30 minutes, for 10 days. At the end of the treatment the lesions had disappeared. The results suggest that the extracts of the leaves, stems and bark of Mouringa oleifera could be used as a natural alternative for the treatment of diabetic patients with limb infection processes with possible pharmaceutical applications.